Incidence of Ureteric injury in complicated cesarean section and late complications - Alaa Hussain (University of Thi-Qar Journal of Science, 2019)
;Most common operation in gynecological department is c/s ,high percentage of c/s are complicatedresulting with many early and late complication, one of intraoperative complication is ureteric injury and or uretericligation. Patients and methods:through 3 years between may 2011- may 2014 on 34 patients get ureteric injury in a complicatedC/S discovered either intra operatively or as an early post operative complication with confirm diagnosis by IVU. thosepatients correct the defect by re anastamosis with ureteric catheterization for two months then fallow up to detect anypost operative ipsilateral renal complication.Results:We get 26 patient (76.4%) was complain from intermittent ipsilateral renal symptoms , repeated U/S showingipsilateral mild dilated PCS with chronic U.T.I in general urine examination.Conclusion:Ureteric injury may lead to chronic complaining of the patients from chronic U.T.I and a sequence ofureteric stenosis , so we advise that in any complicated C/S we need a urosurgical doctor in addition to the gynecologistsurgeon to avoid as much as possible ureteric injury.